Promises and Lies: Speech Act Analysis of Character Dialogue in The Great Gatsby - Ergi Wian Septiandiko; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2025)
Characters in literature perform actions that influence stories in addition to communicating information. Scholars have yet to fully examine the speech act aspect of character interactions in F. Scott Fitzgerald's The Great Gatsby. In order to close this gap, this study looks at how lies and promises in The Great Gatsby serve as illocutionary acts that highlight important themes and disclose interpersonal dynamics. The analysis, which is based on Speech Act Theory (Austin and Searle), focusses on insincere assertives (lies) and commissives (promises) in a few dialogue exchanges, especially those involving Jay Gatsby and Daisy Buchanan. The study explores how characters' verbal promises and lies propel the story and represent themes of delusion, idealism, treachery, and the American Dream through a qualitative analysis of these exchanges. The analysis shows that Daisy's broken promises and Gatsby's extravagant promises and made-up backstory are more than just empty rhetoric; they deliberately create illusions and reveal hidden power dynamics and emotional undertones in the relationships between the characters. Fitzgerald's criticism of illusion and disillusionment is ultimately highlighted by this pragmatic lens, which also demonstrates how crucial the speech acts of characters that promise and lie are to comprehending the novel's messages about trust, treachery, and the American Dream.